Evaluation of Nigella sativa Thymoquinone Extract as a Protective Agent Against Acetaminophen-Induced Hepatic Injury in Rats: Thymoquinone Extract Protect Against Acetaminophen-Induced Hepatic Injury in Rats - Khairi, Bashaer (Libyan Journal of Medical and Applied Sciences, 2026)
Acetaminophen overdose, mainly showing mitochondrial damage, oxidative stress and inflammation still remains one of the leading causes of drug induced liver injury in worldwide. Thymoquinone (TQ) has been identified as the major bioactive component of Nigella sativa, which exhibits various biological, antioxidant and cytoprotective effects. The study aimed to evaluate the hepatoprotective effect of thymoquinone extract from Nigella sativa against acetaminophen-induced hepatotoxicity. The experimental design incorporates histopathological analysis, oxidative stress biomarkers, and biochemical liver function tests. According to experimental data, pretreatment with thymoquinone significantly reduces the elevation of liver enzymes caused by APAP, restores antioxidant defense systems, lowers lipid peroxidation, and maintains the histological architecture of the liver. These results support the potential of thymoquinone as a natural hepatoprotective agent against acetaminophen -related liver damage.